Determinan Organizational Citizenship Behaviour oleh Iklim Organisasi dan Gaya Kepemimpinan Transformasional - Ferdinandus, Leonora; Tjokro, Cynthia Imelda (Journal of Business Application, 2023)
This study aims to examine and analyze the influence of transformational leadership style and working conditions on the behavior of extra employees of the Ambon Class I Harbormaster and Port Authority Patrol and Encoding Section. This survey data collection used a questionnaire instrument with a total sample of 41 employees obtained using a census sample technique. The test results using multiple linear regression analysis techniques show that; transformational leadership style and working conditions proved to have a positive and significant effect on extra-role behavior of Ambon Class I Harbormaster and Port Authority employees in the Patrol and Encryption Section. This means that the encouragement of increased leadership transformation and working conditions will increase the extra behavior of employees of Ambon Class I Harbor Patrol and Encryption employees